Arne Skorping; The population dynamics of Elaphostrongylus rangiferi in the intermediate host - an experimental study - Skjenneberg (ed.), Sven (Rangifer, 1987)
Arne Skorping successfully defended his thesis for the Dr. philos degree at the University of Tromsø, Norway, September 12, 1986.